Estudo experimental para validação de métodos para dimensionamento de microrreservatório - Nunes, Eduardo Paslauski (2023)
Urban drainage is fundamental for the planning and expansion of cities. Currently, several cities have regulations for the adoption of low-impact construction practices for source control, associated with drainage systems, such as microreservoirs. The city of Santa Maria (Rio Grande do Sul) has regulations for the adoption of source control systems. However, the existing legislation lacks studies that support the design criteria for these structures, based on the reality of the region. In this context, this research evaluated the capacity of a microreservoir, with a volume of 3.0 m³, to cushion the surface runoff of precipitation events. The structure is installed on the Campus of the Federal University of Santa Maria, in the city of Santa Maria. 33 precipitation events were monitored, from July 2022 to February 2023, with rainfall between 2.40 and 58.20 mm and recurrence times of 1 or 2 years. For the simulations of the behavior of the microreservoirs, the Puls propagation method was used, associated with the Natural Resources Conservation Service (NRCS) method and the modified rational method (MRM) for transforming rainfall into inflow. The results showed that both methods were able to simulate the damping of the peak flow, however the statistical measures of accuracy of the simulated water height in relation to that monitored inside the microreservoir indicated that the NRCS/Puls presents a superior performance than the MRM /Puls, especially for higher volumes of precipitation. It was also verified that in no event did the structure overflow, with the microreservoir being able to cushion the precipitation events that occurred in the period, with an average reduction of 47% in the peak flow for the MRM/Puls and of 57% for NRCS/Puls.